(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Intensification and extensification strategy are an effort to extract tax revenue. Intensification refers to an activity to optimize tax revenue collection for objects and subjects that have been recorded or registered in DJP administration, whereas extensification is an effort to explore new sources of local revenue. The purpose of this study is to illustrate the efforts to increase regional own-source revenue (PAD) through the intensification and the extensification strategies towards entertainment tax revenue in Makassar City. The research method applied is descriptive qualitative research. The results of this study indicate that the intensification and extensification strategy has generally been running quite optimally, but there are still parts that need to be addressed, such as the entertainment tax regulations and tariff setting. These are to increase the number of entertainment taxpayers that are currently not optimal. According to data, the number of mandatorily registered taxpayers in 2017 was 30 people, while it dropped to 25 people in 2018. As for the tax collection system, the procedures for determining taxes and the accounting system have been very effective in supporting the improvement of the original revenue of Makassar City.